Quantifying per- and polyfluoroalkyl substances (PFAS) in air emissions: Lab & field experiences from a hazardous waste incinerator - Jelle Hofman; Griet Jacobs; Bart Baeyens; Aline Reis De Carvalho; Wim Aerts; Stefan Voorspoels; Gill Van den Bergh; Masha Van Deun; Patrick Berghmans; Andres Van Brecht; Gert Otten (Environment International)
Per- and polyfluoroalkyl substances (PFAS) are ubiquitous in our environment and food chains but standardized monitoring methods are still lacking for the air compartment. This work presents methodological developments and validation experiments which led to a new compendium method (LUC) for the quantification of PFAS in air emissions. From 2021 onwards, relevant experience with the proposed OTM-45 method (EPA, 2021) was obtained through dedicated laboratory experiments and 15 repeated stack measurements at a hazardous waste-to-energy (WtE) plant. We optimized the sampling, extraction and analytical procedure and performed different lab and field validation exercises, resulting in the first available regulatory method for the detection and quantification of PFAS in air emissions (LUC/VI/003). This method turned into force in Flanders since January 15th, 2024, and is meanwhile applied on various stacks and industries to collect evidence on prevailing concentration levels, compositional fingerprints and impact evaluation from gas abatement technologies. We stress the need for harmonization of both PFAS sampling and analytical procedures in order to guarantee comparability of PFAS emission results. This methodological evidence paves the way for more standardized emission monitoring, more stringent environmental standards and improved public health protection.